The Efectiveness of Nonwoven Kenaf Geotextile in Improving Load Bearing of Soft Soil - Abdulkrem, Abdulrahman Zahid; A Rashid, Ahmad Safuan; Amhad, Talal; Mat Said, Khairun Nissa; Abdul Rashid, Azrin Hani; Ismail, Afqah; Dehghanbanadaki, Ali (springer, 2025)
Synthetic fbres are commonly used to make geotextiles for geotechnical applications, but they are made from non-renewable resources such as petroleum, adversely afecting the environment. To address this issue, bio-based geotextiles that depend on locally available natural resources can be used as a more sustainable alternative. In this study, a nonwoven kenaf polypropylene geotextile was manufactured from waste products from the kenaf industry and tested to determine its engineering characteristics. The kenaf was blended with polypropylene to ease the fabrication process and enhance its durability. Several physical modelling tests were then conducted to evaluate the performance of this type of geotextile in improving the load-carrying capacity of cohesive soils in sites and projects. Using this geotextile resulted in an improvement of 15.2 to 46.5% in the bearing capacity of soft soil, making it a viable replacement for synthetic geotextiles in projects with a limited lifespan. The laboratory results were validated using fnite element software which showed that the numerical results closely followed the experimental results for the ultimate bearing capacity values with the highest variation of 18%. The geotextile layer’s optimum depth was 0.25 times the footing width (0.25B). Based on the results of this study, nonwoven kenaf geotextile can be considered a partially sustainable material and an eco-friendly solution for ground improvement practices. However, further investigation should be carried out to determine the durability of the nonwoven kenaf geotextile.